A mattress material based on natural mineral crystals and preparation method thereof

By using porous photocatalytic crystal materials and magnetic iron tetraoxide in the mattress, combined with chitosan-gel hydrogel, the problem of natural crystals regulating health and air quality in the mattress is solved, and antibacterial Improved mite and insect resistance performance and the generation of far-infrared waves have improved sleep quality and immunity.

CN118373941BActive Publication Date: 2024-12-13ZHENGQI NEW MATERIALS TECHNOLOGY (CHANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410825789.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2024-12-13
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The addition of existing natural crystals to the mattress cannot effectively regulate human health and indoor air quality, and there are problems of insufficient antibacterial, anti-mites and insect resistance.

Method used

Porous photocatalytic crystal material is prepared by sol-gel reaction, magnetic iron tetroxide is deposited on the surface, copper oxide, manganese oxide and rare earth oxide are added, and combined with chitosan-gel hydrogel, acrylamide and crosslinking agent are added , perform photocuring to produce mattress materials based on natural mineral crystals.

Benefits of technology

The mattress material has the function of regulating the temperature and humidity of the sleeping body. It has good antibacterial, anti-mites and insect resistance. It can generate far-infrared waves and magnetic fields, improve blood circulation, improve immunity, and purify environmental gases. It is very popular among consumers. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention proposes a mattress material based on natural mineral crystals and a preparation method thereof, and belongs to the technical field of crystal materials. A porous photocatalytic crystal material is prepared by sol-gel reaction, magnetic ferrosoferric oxide is deposited on the surface, modified by a silane coupling agent, copper oxide, manganese oxide and rare earth oxide are attached, calcined, added to chitosan-gelatin hydrogel, acrylamide is added, an initiator and a cross-linking agent are added, heated and stirred to react, and light-cured to obtain a mattress material based on natural mineral crystals. The mattress material based on natural mineral crystals prepared by the present invention has low cost, can adjust sleeping body temperature and humidity, has good comfort, good antibacterial, anti-insect and anti-mite properties, good durability, emits far-infrared waves and generates magnetic fields, generates negative ions to improve human health, purifies environmental gases, and is deeply loved by consumers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crystal materials, and in particular to a mattress material based on natural mineral crystals and a preparation method thereof. Background Art

[0002] With the continuous improvement of living standards, people are paying more and more attention to hygienic, safe and healthy products. As people's pace of life is accelerating and the pressure of life is relatively high, more and more people are in a sub-healthy state. However, due to the high pressure of life, work and life take up a lot of time and there is no spare time to maintain and regulate their bodies. Therefore, a product that can regulate health without taking up free time has been loved by more and more people, and the mattress used during sleep has become the first choice if it can regulate human health.

[0003] Natural crystal is a quartz crystal mineral. Its main chemical component is silicon dioxide, with the chemical formula SiO2. It is also known as water crystal, water jade, and water jade. Well-developed single crystals are hexagonal pyramids, so they are usually blocky or granular aggregates. Natural crystal can affect physical health by generating electromagnetic fields and regulating the human aura, which is the so-called "mineral therapy". Secondly, natural crystal can also collect negative ions from the outside and release them into the surrounding environment, thereby improving indoor air quality and relieving symptoms such as headaches and insomnia.

[0004] However, directly adding natural crystals into mattresses does not have a good effect in regulating health, so they need to be modified. Summary of the invention

[0005] The purpose of the present invention is to propose a mattress material based on natural mineral crystals and a preparation method thereof, which has low cost, can regulate sleeping body temperature and humidity, has good comfort, has good antibacterial, anti-insect and anti-mite properties, has good durability, emits far-infrared waves and generates magnetic fields, generates negative ions to improve human health, purifies environmental gases, and is deeply loved by consumers.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The invention provides a preparation method of a mattress material based on natural mineral crystals. A porous photocatalytic crystal material is prepared by a sol-gel reaction, magnetic ferrosoferric oxide is deposited on the surface, the material is modified by a silane coupling agent, copper oxide, manganese oxide and rare earth oxide are attached, the material is calcined, the material is added to a chitosan-gelatin hydrogel, acrylamide, an initiator and a cross-linking agent are added, the material is heated and stirred for reaction, and the material is photocured to obtain the mattress material based on natural mineral crystals.

[0008] As a further improvement of the present invention, the following steps are included:

[0009] S1. Preparation of porous photocatalytic crystal material: ball-milling natural mineral crystals, sieving, adding to ethanol, adding alkyl orthosilicate, tetrabutyl titanate, porogen and thiourea, stirring and mixing evenly, dropping ammonia solution, stirring and reacting, centrifuging, washing, ball-milling, calcining, and obtaining a porous photocatalytic crystal material;

[0010] S2. Deposition of magnetic particles: The porous photocatalytic crystal material obtained in step S1 is added to water, ferric chloride and ferrous chloride are added, stirred and mixed evenly, ammonia is added dropwise, stirred for reaction, aged, filtered, washed, and dried to obtain a porous magnetic photocatalytic crystal material;

[0011] S3 ceramic powder attachment: The step S2 prepared magnetic porous photocatalytic crystal material, copper oxide powder, manganese oxide powder, rare earth oxides were mixed, calcined, ball milled, sieved to obtain a ceramic magnetic crystal powder;

[0012] S4. Preparation of modified powder: The ceramic magnetic crystal powder obtained in step S2 was added to ethanol, a composite silane coupling agent was added, the reaction was heated and stirred, filtered, washed, and dried to obtain a modified powder;

[0013] S5. Preparation of mattress materials based on natural mineral crystals: dissolve carboxymethyl chitosan in water, add gelatin and the modified powder obtained in step S4, stir and mix evenly, add acrylamide, stir and mix evenly, add initiator and cross-linking agent, heat and stir to react under inert gas protection, pour into a mold, and cure with ultraviolet light to obtain a mattress material based on natural mineral crystals.

[0014] As a further improvement of the present invention, the mesh number of the sieve in step S1 is 150-200 mesh, the mass ratio of the natural mineral crystals, alkyl orthosilicate, tetrabutyl titanate, porogen, thiourea, and ammonia water is 15-20:7-10:4-7:0.5-1:0.2-0.3:12-15, the concentration of the ammonia water is 10-15wt%, the stirring reaction time is 1-3h, the ball milling time is 1-2h, the calcination temperature is 550-650°C, the time is 1-3h, and the porogen is at least one of hexadecyltrimethylammonium chloride, hexadecyltrimethyl sodium chloride, hexadecyldimethylbenzyl ammonium chloride, and hexadecyldimethylbenzyl sodium chloride.

[0015] As a further improvement of the present invention, the mass ratio of the porous photocatalytic crystal material, ferric chloride, ferrous chloride and ammonia water in step S2 is 30-50:6.4-6.5:2.4-2.6:4-6, the concentration of ammonia water is 25-30wt%, the temperature of the stirring reaction is 65-75°C, the time is 3-5h, and the aging time is 1-2h.

[0016] As a further improvement of the present invention, the mass ratio of the magnetic porous photocatalytic crystal material, copper oxide powder, manganese oxide powder and rare earth oxide in step S3 is 50:3-5:2-4:1-2, the calcination temperature is 1200-1300°C, the time is 30-40min, the ball milling time is 1-2h, and the rare earth oxide includes yttrium oxide and lanthanum oxide in a mass ratio of 2-4:3-5.

[0017] As a further improvement of the present invention, the mass ratio of the ceramic magnetic crystal powder and the composite silane coupling agent in step S4 is 100:15-17, the composite silane coupling agent is selected from at least one of KH550, KH560, KH570, A151, A171, KH580, KH590, KH602, and KH792, preferably, a mixture of KH570 and KH560, with a mass ratio of 7-10:4-7, and the temperature of the heating and stirring reaction is 40-50° C., and the time is 1-3 h.

[0018] As a further improvement of the present invention, the mass ratio of carboxymethyl chitosan, gelatin, modified powder, acrylamide, initiator and cross-linking agent in step S5 is 12-15:8-10:10-12:13-18:0.1-0.2:1-2, the initiator is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate, the cross-linking agent is N,N'-methylenebisacrylamide, the temperature of the heating and stirring reaction is 50-60°C, the time is 3-5h, and the curing time is 1-2h.

[0019] As a further improvement of the present invention, the present invention specifically comprises the following steps:

[0020] S1. Preparation of porous photocatalytic crystal material: 15-20 parts by weight of natural mineral crystals are ball-milled and passed through a 150-200 mesh sieve, added to ethanol, 7-10 parts by weight of alkyl orthosilicate, 4-7 parts by weight of tetrabutyl titanate, 0.5-1 parts by weight of a porogen and 0.2-0.3 parts by weight of thiourea are added, stirred and mixed evenly, 12-15 parts by weight of a 10-15wt% ammonia solution is added dropwise, stirred and reacted for 1-3h, centrifuged, washed, ball-milled for 1-2h, and calcined at 550-650°C for 1-3h to obtain a porous photocatalytic crystal material;

[0021] S2. Deposition of magnetic particles: 30-50 parts by weight of the porous photocatalytic crystal material prepared in step S1 is added to 200 parts by weight of water, 6.4-6.5 parts by weight of ferric chloride and 2.4-2.6 parts by weight of ferrous chloride are added, the mixture is stirred and mixed evenly, 4-6 parts by weight of 25-30wt% ammonia water is added dropwise, the reaction is stirred at 65-75°C for 3-5h, aged for 1-2h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material;

[0022] S3. Ceramic powder attachment: 50 parts by weight of the magnetic porous photocatalytic crystal material obtained in step S2, 3-5 parts by weight of copper oxide powder, 2-4 parts by weight of manganese oxide powder, 1-2 parts by weight of rare earth oxides are mixed uniformly, calcined at 1200-1300 ° C for 30-40min, ball milled for 1-2h, and sieved to obtain a ceramic magnetic crystal powder;

[0023] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 2-4:3-5;

[0024] S4. Preparation of modified powder: 100 parts by weight of the ceramic magnetic crystal powder obtained in step S3 was added to 500 parts by weight of ethanol, 15-17 parts by weight of a composite silane coupling agent was added, heated to 40-50 ° C, stirred for 1-3h, filtered, washed, and dried to obtain a modified powder;

[0025] The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 7-10:4-7;

[0026] S5. Preparation of mattress materials based on natural mineral crystals: dissolve 12-15 parts by weight of carboxymethyl chitosan in 500 parts by weight of water, add 8-10 parts by weight of gelatin and 10-12 parts by weight of the modified powder obtained in step S4, stir and mix evenly, add 13-18 parts by weight of acrylamide, stir and mix evenly, add 0.1-0.2 parts by weight of initiator and 1-2 parts by weight of cross-linking agent N,N'-methylenebisacrylamide, heat to 50-60°C under inert gas protection, stir and react for 3-5 hours, pour into a mold, and UV-cure for 1-2 hours to obtain a mattress material based on natural mineral crystals.

[0027] The present invention further protects a mattress material based on natural mineral crystals obtained by the above-mentioned preparation method.

[0028] The present invention further protects the use of the above-mentioned mattress material based on natural mineral crystals in the preparation of mattresses.

[0029] The present invention has the following beneficial effects:

[0030] The present invention uses natural mineral crystals as cores, and then coats a layer of TiO2 / SiO2 on its surface through sol-gel reaction. At the same time, by introducing thiourea, the S / C doped in the prepared TiO2 changes the electron transition energy level, so that TiO2 can use visible light catalysis, thereby improving the antibacterial and anti-mite performance of the mattress material, as well as air purification and adsorption of harmful gases in the air, and safety and environmental protection. Natural mineral crystals can affect physical health by generating electromagnetic fields, regulating the human body's aura, etc., which is the so-called "mineral therapy". Secondly, natural mineral crystals can also collect negative ions from the outside and release them into the surrounding environment, thereby improving indoor air quality and relieving symptoms such as headaches and insomnia. At the same time, the prepared porous photocatalytic crystal material has a large specific surface area and contains countless tiny holes, which can not only regulate indoor humidity, but also absorb moisture (or sweat) released by the human body during sleep, play a dry role, and thus improve sleep quality.

[0031] Magnetic particles and ceramic powders are deposited on the surface, among which transition metal oxides (magnetic ferroferric oxide, copper oxide and manganese oxide) and rare earth oxides (yttrium oxide and lanthanum oxide) work synergistically and have the characteristics of low raw material cost and stable performance. Magnetic ferroferric oxide can generate a magnetic field, and the combined powder can generate far-infrared waves. Far-infrared waves can penetrate the skin, improve blood circulation, enhance metabolic function, reduce nerve excitability, relieve mild pain, improve pain caused by diseases such as arthritis and muscle spasms, activate the human immune system, improve immunity, and reduce the occurrence of infectious diseases. At the same time, it can also relieve local inflammation caused by infection. It also has the functions of promoting cell regeneration, promoting wound healing, enhancing metabolic capacity, and promoting vasodilation.

[0032] The prepared ceramic magnetic crystal powder is modified by KH560 and KH570 so that the powder surface has double bonds and epoxy groups, the double bonds can be polymerized with acrylamide at the same time, and the epoxy groups can react with the amino groups of chitosan, thereby promoting the dispersibility of the modified powder in the gel, so that the modified powder can be evenly dispersed in the gel, which plays a role in promoting cross-linking and improving mechanical properties.

[0033] The mattress material of the present invention is mainly gel material. The chitosan-gelatin-polyacrylamide hydrogel of the present invention has good mechanical strength and curing performance, good flexibility, making the mattress soft and comfortable, and has good antibacterial, mite and insect removal properties, good durability, and high moisture content. The body temperature of the human body will rise due to the circulation of blood during sleep, thereby affecting the comfort of sleep. In the present invention, the gel molecules in the polymer gel can effectively absorb the heat generated in the human body and discharge it out of the body, and then use conductivity to diffuse to the entire mattress, and circulate continuously, which not only achieves the degree of cooling the human body and comfortable sleep, but also achieves the effect of cooling in summer. The heat dissipation process is slow and will not cause discomfort to the human body. A waterproof isolation film will be provided at the position where the cloth contacts the inside to prevent the volatilization of the water in the gel, and at the same time make it difficult for the molecules of the gel to move, thereby improving the comfort and application effect.

[0034] The mattress material based on natural mineral crystals prepared by the present invention has low cost, can regulate sleeping body temperature and humidity, has good comfort, has good antibacterial, anti-insect and anti-mite properties, has good durability, emits far-infrared waves and generates magnetic fields, generates negative ions to improve human health, and purifies environmental gases, and is deeply loved by consumers. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The natural mineral crystals are mixed ores containing natural crystals and rare earth concentrates with a mass ratio of 10:5. The natural crystals were purchased from Lianyungang Haisheng Quartz Technology Co., Ltd., and the rare earth concentrates were purchased from China North Rare Earth Group High-Tech Co., Ltd.

[0037] Example 1

[0038] This embodiment provides a mattress material based on natural mineral crystals, which specifically includes the following steps:

[0039] S1. Preparation of porous photocatalytic crystal material: 15 g of natural mineral crystal was ball-milled and passed through a 150-mesh sieve, added to 200 g of ethanol, 7 g of methyl orthosilicate, 4 g of tetrabutyl titanate, 0.5 g of hexadecyltrimethylammonium chloride and 0.2 g of thiourea were added, stirred and mixed for 20 min, 12 g of 10 wt % ammonia solution was added dropwise, stirred and reacted for 1 h, centrifuged, washed, ball-milled for 1 h, and calcined at 550 ° C for 1 h to obtain a porous photocatalytic crystal material;

[0040] S2. Deposition of magnetic particles: 30 g of the porous photocatalytic crystal material prepared in step S1 was added to 200 g of water, 6.4 g of ferric chloride and 2.4 g of ferrous chloride were added, and the mixture was stirred for 15 min, 4 g of 25 wt % ammonia was added dropwise, and the reaction was stirred at 65 ° C for 3 h, aged for 1 h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material;

[0041] S3 ceramic powder attachment: 50g of the magnetic porous photocatalytic crystal material obtained in step S2, 3g of copper oxide powder, 2g of manganese oxide powder, 1g of rare earth oxide were mixed for 15min, calcined at 1200°C for 30min, ball milled for 1h, sieved to obtain ceramic magnetic crystal powder;

[0042] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 2:3;

[0043] S4. Preparation of modified powder: 100 g of the ceramic magnetic crystal powder obtained in step S3 was added to 500 g of ethanol, 15 g of a composite silane coupling agent was added, heated to 40 ° C, stirred for 1 h, filtered, washed, and dried to obtain a modified powder;

[0044] The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 7:4;

[0045] S5. Preparation of mattress materials based on natural mineral crystals: dissolve 12g of carboxymethyl chitosan in 500g of water, add 8g of gelatin and 10g of the modified powder obtained in step S4, stir and mix for 15min, add 13g of acrylamide, stir and mix for 10min, add 0.1g of potassium persulfate and 1g of cross-linking agent N,N'-methylenebisacrylamide, heat to 50°C under nitrogen protection, stir and react for 3h, pour into a mold, and cure under UV light for 1h to obtain a mattress material based on natural mineral crystals.

[0046] Example 2

[0047] This embodiment provides a mattress material based on natural mineral crystals, which specifically includes the following steps:

[0048] S1. Preparation of porous photocatalytic crystal material: 20g natural mineral crystal was ball-milled and passed through a 200-mesh sieve, added to 200g ethanol, 10g tetraethyl orthosilicate, 7g tetrabutyl titanate, 1g hexadecyl dimethyl benzyl sodium chloride and 0.3g thiourea were added, stirred and mixed for 20min, 15g 15wt% ammonia solution was added dropwise, stirred and reacted for 3h, centrifuged, washed, ball-milled for 2h, and calcined at 650℃ for 3h to obtain a porous photocatalytic crystal material;

[0049] S2. Deposition of magnetic particles: 50 g of the porous photocatalytic crystal material prepared in step S1 was added to 200 g of water, 6.5 g of ferric chloride and 2.6 g of ferrous chloride were added, and the mixture was stirred for 15 min, 6 g of 30 wt % ammonia was added dropwise, and the reaction was stirred at 75 ° C for 5 h, aged for 2 h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material;

[0050] S3 ceramic powder attachment: 50g of the magnetic porous photocatalytic crystal material obtained in step S2, 5g of copper oxide powder, 4g of manganese oxide powder, 2g of rare earth oxide were mixed for 15min, calcined at 1300°C for 40min, ball milled for 2h, sieved to obtain ceramic magnetic crystal powder;

[0051] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 4:5;

[0052] S4. Preparation of modified powder: 100 g of the ceramic magnetic crystal powder obtained in step S3 was added to 500 g of ethanol, 17 g of a composite silane coupling agent was added, heated to 50 ° C, stirred for 3 h, filtered, washed, and dried to obtain a modified powder;

[0053] The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 10:7;

[0054] S5. Preparation of mattress materials based on natural mineral crystals: dissolve 15g of carboxymethyl chitosan in 500g of water, add 10g of gelatin and 12g of the modified powder obtained in step S4, stir and mix for 15min, add 18g of acrylamide, stir and mix for 10min, add 0.2g of potassium persulfate and 2g of cross-linking agent N,N'-methylenebisacrylamide, heat to 60°C under nitrogen protection, stir and react for 5h, pour into a mold, and UV-cure for 2h to obtain a mattress material based on natural mineral crystals.

[0055] Example 3

[0056] This embodiment provides a mattress material based on natural mineral crystals, which specifically includes the following steps:

[0057] S1. Preparation of porous photocatalytic crystal material: 17g natural mineral crystal was ball-milled and passed through a 200-mesh sieve, added to 200g ethanol, 8.5g tetraethyl orthosilicate, 5.5g tetrabutyl titanate, 0.7g hexadecyltrimethyl sodium chloride and 0.25g thiourea were added, stirred and mixed for 20min, 13.5g 12wt% ammonia solution was added dropwise, stirred and reacted for 2h, centrifuged, washed, ball-milled for 1.5h, and calcined at 600℃ for 2h to obtain a porous photocatalytic crystal material;

[0058] S2. Deposition of magnetic particles: 40 g of the porous photocatalytic crystal material prepared in step S1 was added to 200 g of water, 6.45 g of ferric chloride and 2.5 g of ferrous chloride were added, and the mixture was stirred for 15 min. 5 g of 27 wt % ammonia was added dropwise, and the mixture was stirred at 70 ° C for 4 h, aged for 1.5 h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material;

[0059] S3 ceramic powder attachment: 50g of the magnetic porous photocatalytic crystal material obtained in step S2, 4g of copper oxide powder, 3g of manganese oxide powder, 1.5g of rare earth oxide were mixed for 15min, calcined at 1250°C for 35min, ball milled for 1.5h, and sieved to obtain a ceramic magnetic crystal powder;

[0060] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 3:4;

[0061] S4. Preparation of modified powder: 100 g of the ceramic magnetic crystal powder obtained in step S3 was added to 500 g of ethanol, 16 g of a composite silane coupling agent was added, heated to 45 ° C, stirred for 2 h, filtered, washed, and dried to obtain a modified powder;

[0062] The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 8:5;

[0063] S5. Preparation of mattress materials based on natural mineral crystals: Dissolve 13.5g of carboxymethyl chitosan in 500g of water, add 9g of gelatin and 11g of the modified powder obtained in step S4, stir and mix for 15min, add 15g of acrylamide, stir and mix for 10min, add 0.15g of sodium persulfate and 1.5g of cross-linking agent N,N'-methylenebisacrylamide, heat to 55°C under nitrogen protection, stir and react for 4h, pour into a mold, and UV-cure for 1.5h to obtain a mattress material based on natural mineral crystals.

[0064] Example 4

[0065] Compared with Example 3, the difference is that the composite silane coupling agent is replaced by a single KH570.

[0066] Example 5

[0067] Compared with Example 3, the difference is that the composite silane coupling agent is replaced by a single KH560.

[0068] Example 6

[0069] Compared with Example 3, the difference is that the rare earth oxide is single yttrium oxide.

[0070] Example 7

[0071] Compared with Example 3, the difference is that the rare earth oxide is a single lanthanum oxide.

[0072] Comparative Example 1

[0073] Compared with Example 3, the difference is that tetraethyl orthosilicate is not added in step S1.

[0074] The details are as follows:

[0075] S1. Preparation of porous photocatalytic crystal material: 17 g of natural mineral crystals were ball-milled and passed through a 200-mesh sieve, added to 200 g of ethanol, 14 g of tetrabutyl titanate, 0.7 g of hexadecyltrimethyl sodium chloride and 0.25 g of thiourea, stirred and mixed for 20 min, 13.5 g of 12 wt% ammonia solution was added dropwise, stirred and reacted for 2 h, centrifuged, washed, ball-milled for 1.5 h, and calcined at 600 ° C for 2 h to obtain a porous photocatalytic crystal material.

[0076] Comparative Example 2

[0077] Compared with Example 3, the difference is that tetrabutyl titanate is not added in step S1.

[0078] The details are as follows:

[0079] S1. Preparation of porous crystal material: 17 g of natural mineral crystal was ball-milled and passed through a 200-mesh sieve, added to 200 g of ethanol, 14 g of tetraethyl orthosilicate, 0.7 g of hexadecyltrimethyl sodium chloride and 0.25 g of thiourea were added, and the mixture was stirred for 20 min. 13.5 g of 12 wt% ammonia solution was added dropwise, and the mixture was stirred for 2 h. The mixture was centrifuged, washed, ball-milled for 1.5 h, and calcined at 600 °C for 2 h to obtain a porous crystal material.

[0080] Comparative Example 3

[0081] Compared with Example 3, the difference is that thiourea is not added in step S1.

[0082] The details are as follows:

[0083] S1. Preparation of porous photocatalytic crystal material: 17 g of natural mineral crystals were ball-milled and passed through a 200-mesh sieve, added to 200 g of ethanol, 8.5 g of tetraethyl orthosilicate, 5.5 g of tetrabutyl titanate, and 0.7 g of hexadecyltrimethyl sodium chloride were added, and the mixture was stirred for 20 min. 13.5 g of 12 wt % ammonia solution was added dropwise, and the reaction was stirred for 2 h. The mixture was centrifuged, washed, ball-milled for 1.5 h, and calcined at 600 ° C for 2 h to obtain a porous photocatalytic crystal material.

[0084] Comparative Example 4

[0085] Compared with Example 3, the difference is that step S2 is not performed.

[0086] The details are as follows:

[0087] S1. Preparation of porous photocatalytic crystal material: 17g natural mineral crystal was ball-milled and passed through a 200-mesh sieve, added to 200g ethanol, 8.5g tetraethyl orthosilicate, 5.5g tetrabutyl titanate, 0.7g hexadecyltrimethyl sodium chloride and 0.25g thiourea were added, stirred and mixed for 20min, 13.5g 12wt% ammonia solution was added dropwise, stirred and reacted for 2h, centrifuged, washed, ball-milled for 1.5h, and calcined at 600℃ for 2h to obtain a porous photocatalytic crystal material;

[0088] S2. Ceramic powder adhesion: 50 g of the porous photocatalytic crystal material obtained in step S1, 4 g of copper oxide powder, 3 g of manganese oxide powder, and 1.5 g of rare earth oxide were mixed for 15 min, calcined at 1250 ° C for 35 min, ball milled for 1.5 h, and sieved to obtain ceramic crystal powder;

[0089] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 3:4;

[0090] S3. Preparation of modified powder: 100 g of the ceramic crystal powder obtained in step S2 was added to 500 g of ethanol, 16 g of a composite silane coupling agent was added, heated to 45 ° C, stirred for 2 h, filtered, washed, and dried to obtain a modified powder;

[0091] The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 8:5;

[0092] S4. Preparation of mattress materials based on natural mineral crystals: Dissolve 13.5g of carboxymethyl chitosan in 500g of water, add 9g of gelatin and 11g of the modified powder obtained in step S3, stir and mix for 15min, add 15g of acrylamide, stir and mix for 10min, add 0.15g of sodium persulfate and 1.5g of cross-linking agent N,N'-methylenebisacrylamide, heat to 55°C under nitrogen protection, stir and react for 4h, pour into a mold, and UV-cure for 1.5h to obtain a mattress material based on natural mineral crystals.

[0093] Comparative Example 5

[0094] Compared with Example 3, the difference is that no rare earth oxide is added in step S3.

[0095] The details are as follows:

[0096] S3. Attachment of ceramic powder: 50 g of the magnetic porous photocatalytic crystal material obtained in step S2, 4 g of copper oxide powder, and 3 g of manganese oxide powder were mixed for 15 min, calcined at 1250° C. for 35 min, ball-milled for 1.5 h, and sieved to obtain ceramic magnetic crystal powder.

[0097] Comparative Example 6

[0098] Compared with Example 3, the difference is that step S4 is not performed.

[0099] The details are as follows:

[0100] S1. Preparation of porous photocatalytic crystal material: 17g natural mineral crystal was ball-milled and passed through a 200-mesh sieve, added to 200g ethanol, 8.5g tetraethyl orthosilicate, 5.5g tetrabutyl titanate, 0.7g hexadecyltrimethyl sodium chloride and 0.25g thiourea were added, stirred and mixed for 20min, 13.5g 12wt% ammonia solution was added dropwise, stirred and reacted for 2h, centrifuged, washed, ball-milled for 1.5h, and calcined at 600℃ for 2h to obtain a porous photocatalytic crystal material;

[0101] S2. Deposition of magnetic particles: 40 g of the porous photocatalytic crystal material prepared in step S1 was added to 200 g of water, 6.45 g of ferric chloride and 2.5 g of ferrous chloride were added, and the mixture was stirred for 15 min. 5 g of 27 wt % ammonia was added dropwise, and the mixture was stirred at 70 ° C for 4 h, aged for 1.5 h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material;

[0102] S3 ceramic powder attachment: 50g of the magnetic porous photocatalytic crystal material obtained in step S2, 4g of copper oxide powder, 3g of manganese oxide powder, 1.5g of rare earth oxide were mixed for 15min, calcined at 1250°C for 35min, ball milled for 1.5h, and sieved to obtain a ceramic magnetic crystal powder;

[0103] The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 3:4;

[0104] S4. Preparation of mattress materials based on natural mineral crystals: Dissolve 13.5g of carboxymethyl chitosan in 500g of water, add 9g of gelatin and 11g of the ceramic magnetic crystal powder obtained in step S3, stir and mix for 15min, add 15g of acrylamide, stir and mix for 10min, add 0.15g of sodium persulfate and 1.5g of cross-linking agent N,N'-methylenebisacrylamide, heat to 55°C under nitrogen protection, stir and react for 4h, pour into a mold, and UV-cure for 1.5h to obtain a mattress material based on natural mineral crystals.

[0105] Comparative Example 7

[0106] Compared with Example 3, the difference is that carboxymethyl chitosan is not added in step S5.

[0107] The details are as follows:

[0108] S5. Preparation of mattress materials based on natural mineral crystals: Dissolve 22.5 g of gelatin in 500 g of water, add 11 g of the modified powder obtained in step S4, stir and mix for 15 min, add 15 g of acrylamide, stir and mix for 10 min, add 0.15 g of sodium persulfate and 1.5 g of cross-linking agent N,N'-methylenebisacrylamide, heat to 55°C under nitrogen protection, stir and react for 4 h, pour into a mold, and UV-cure for 1.5 h to obtain a mattress material based on natural mineral crystals.

[0109] Test Example 1

[0110] The ceramic magnetic crystal powder obtained in step S3 of Examples 1-3, 6, 7 and Comparative Example 1-5 of the present invention was measured for dual-band infrared emissivity of 3μm-5μm and 8μm-14μm at room temperature using an IR-2 dual-band emissivity measuring instrument. The results are shown in Table 1.

[0111] Table 1

[0112]

[0113] It can be seen from the above table that the ceramic magnetic crystal powders prepared in Examples 1-3 of the present invention have high infrared emissivity in dual bands of 3μm-5μm and 8μm-14μm.

[0114] Test Example 2

[0115] The mattress materials based on natural mineral crystals prepared in Examples 1-7 of the present invention and Comparative Examples 1-7 were subjected to mechanical property tests. The results are shown in Table 2.

[0116] Table 2

[0117]

[0118] It can be seen from the above table that the mattress materials based on natural mineral crystals prepared in Examples 1-3 of the present invention have good mechanical properties.

[0119] Test Example 3

[0120] The mattress materials based on natural mineral crystals prepared in Examples 1-7 of the present invention and Comparative Examples 1-7 were subjected to comprehensive performance tests.

[0121] Air permeability test: Test according to GB / T 5453-1997 "Test for air permeability of textile fabrics". Take 10 samples of 30cm×30cm in each group and calculate the average value. The air permeability area of ​​the sample is 20cm 2 , the test pressure difference is 200Pa.

[0122] Compression performance test: GB / T 24442.1-2009 "Determination of compression properties of textiles Part 1: Constant method" was used for testing. 10 samples were taken from each group, and the pressure foot area was 100mm 2 , light pressure 0.5kPa, heavy pressure 30kPa. Calculate the compression rate (%) and compression elasticity (%) of each sample.

[0123] Compression rate (%) = (light compression thickness - heavy compression thickness) / light compression thickness × 100%

[0124] Compression elasticity (%) = (recovery thickness - heavy compression thickness) / (light compression thickness - heavy compression thickness) × 100%

[0125] Abrasion resistance test: GB / T 21196.3-2007 "Martindale method for textiles - Test for abrasion resistance of fabrics - Part 3: Determination of mass loss" was used for the test. The load pressure was 5.82N, the sample diameter was 38mm, the initial friction was 100 times, and the data was recorded every 50 times thereafter until the fabric was worn out. The abrasion resistance index was calculated.

[0126] Wear resistance index (times / mg) = total number of frictions / mass loss of the sample under total number of frictions

[0127] Moisture permeability test: GB / T 12704.1-2009 "Test method for moisture permeability of textile fabrics Part 2: Evaporation method" is used for testing. Pour 34mL of water into the moisture permeability cup and place it in the test instrument for 1 hour. The relative humidity of the test box is 50%, and the relative humidity in the moisture permeability cup is 100%. Test and calculate the moisture permeability of the sample.

[0128] The results are shown in Table 3.

[0129] Table 3

[0130]

[0131] It can be seen from the above table that the mattress materials based on natural mineral crystals prepared in Examples 1-3 of the present invention have good comprehensive properties.

[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a mattress material based on natural mineral crystals, characterized in that: The following steps are involved: S1. Preparation of porous photocatalytic crystal material: ball-milling natural mineral crystals, sieving, adding to ethanol, adding alkyl orthosilicate, tetrabutyl titanate, porogen and thiourea, stirring and mixing evenly, dropping ammonia solution, stirring and reacting, centrifuging, washing, ball-milling, calcining, and obtaining a porous photocatalytic crystal material; The natural mineral crystals are mixed ore containing natural crystals and rare earth concentrates, with a mass ratio of 10:5; S2. Deposition of magnetic particles: The porous photocatalytic crystal material obtained in step S1 is added to water, ferric chloride and ferrous chloride are added, stirred and mixed evenly, ammonia is added dropwise, stirred for reaction, aged, filtered, washed, and dried to obtain a porous magnetic photocatalytic crystal material; S3 ceramic powder attachment: The step S2 prepared magnetic porous photocatalytic crystal material, copper oxide powder, manganese oxide powder, rare earth oxides were mixed, calcined, ball milled, sieved to obtain a ceramic magnetic crystal powder; The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 2-4:3-5; S4. Preparation of modified powder: The ceramic magnetic crystal powder obtained in step S2 was added to ethanol, a composite silane coupling agent was added, the reaction was heated and stirred, filtered, washed, and dried to obtain a modified powder; The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 7-10:4-7; S5. Preparation of mattress materials based on natural mineral crystals: dissolve carboxymethyl chitosan in water, add gelatin and the modified powder obtained in step S4, stir and mix evenly, add acrylamide, stir and mix evenly, add initiator and cross-linking agent, heat and stir to react under inert gas protection, pour into a mold, and cure with ultraviolet light to obtain a mattress material based on natural mineral crystals.

2. The preparation method according to claim 1, characterized in that: The mesh number of the sieve in step S1 is 150-200 mesh, the mass ratio of the natural mineral crystal, alkyl orthosilicate, tetrabutyl titanate, porogen, thiourea, and ammonia water is 15-20:7-10:4-7:0.5-1:0.2-0.3:12-15, the concentration of the ammonia water is 10-15wt%, the stirring reaction time is 1-3h, the ball milling time is 1-2h, the calcination temperature is 550-650°C, the time is 1-3h, and the porogen is at least one of hexadecyltrimethylammonium chloride, hexadecyltrimethyl sodium chloride, hexadecyldimethylbenzyl ammonium chloride, and hexadecyldimethylbenzyl sodium chloride.

3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the porous photocatalytic crystal material, ferric chloride, ferrous chloride and ammonia water is 30-50:6.4-6.5:2.4-2.6:4-6, the concentration of ammonia water is 25-30wt%, the temperature of the stirring reaction is 65-75°C, the time is 3-5h, and the aging time is 1-2h.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the magnetic porous photocatalytic crystal material, copper oxide powder, manganese oxide powder and rare earth oxide is 50:3-5:2-4:1-2, the calcination temperature is 1200-1300° C., the time is 30-40 min, and the ball milling time is 1-2 h.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the ceramic magnetic crystal powder to the composite silane coupling agent is 100:15-17, the temperature of the heating and stirring reaction is 40-50° C., and the time is 1-3 hours.

6. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of carboxymethyl chitosan, gelatin, modified powder, acrylamide, initiator and cross-linking agent is 12-15:8-10:10-12:13-18:0.1-0.2:1-2, the initiator is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate, the cross-linking agent is N,N'-methylenebisacrylamide, the temperature of the heating and stirring reaction is 50-60°C, the time is 3-5h, and the curing time is 1-2h.

7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of porous photocatalytic crystal material: 15-20 parts by weight of natural mineral crystals are ball-milled and passed through a 150-200 mesh sieve, added to ethanol, 7-10 parts by weight of alkyl orthosilicate, 4-7 parts by weight of tetrabutyl titanate, 0.5-1 parts by weight of a porogen and 0.2-0.3 parts by weight of thiourea are added, stirred and mixed evenly, 12-15 parts by weight of a 10-15wt% ammonia solution is added dropwise, stirred and reacted for 1-3h, centrifuged, washed, ball-milled for 1-2h, and calcined at 550-650°C for 1-3h to obtain a porous photocatalytic crystal material; S2. Deposition of magnetic particles: 30-50 parts by weight of the porous photocatalytic crystal material prepared in step S1 is added to 200 parts by weight of water, 6.4-6.5 parts by weight of ferric chloride and 2.4-2.6 parts by weight of ferrous chloride are added, the mixture is stirred and mixed evenly, 4-6 parts by weight of 25-30wt% ammonia water is added dropwise, the reaction is stirred at 65-75°C for 3-5h, aged for 1-2h, filtered, washed, and dried to obtain a magnetic porous photocatalytic crystal material; S3. Ceramic powder attachment: 50 parts by weight of the magnetic porous photocatalytic crystal material obtained in step S2, 3-5 parts by weight of copper oxide powder, 2-4 parts by weight of manganese oxide powder, 1-2 parts by weight of rare earth oxides are mixed uniformly, calcined at 1200-1300 ° C for 30-40min, ball milled for 1-2h, and sieved to obtain a ceramic magnetic crystal powder; The rare earth oxides include yttrium oxide and lanthanum oxide in a mass ratio of 2-4:3-5; S4. Preparation of modified powder: 100 parts by weight of the ceramic magnetic crystal powder obtained in step S3 was added to 500 parts by weight of ethanol, 15-17 parts by weight of a composite silane coupling agent was added, heated to 40-50 ° C, stirred for 1-3h, filtered, washed, and dried to obtain a modified powder; The composite silane coupling agent is a mixture of KH570 and KH560, with a mass ratio of 7-10:4-7; S5. Preparation of mattress materials based on natural mineral crystals: dissolve 12-15 parts by weight of carboxymethyl chitosan in 500 parts by weight of water, add 8-10 parts by weight of gelatin and 10-12 parts by weight of the modified powder obtained in step S4, stir and mix evenly, add 13-18 parts by weight of acrylamide, stir and mix evenly, add 0.1-0.2 parts by weight of initiator and 1-2 parts by weight of cross-linking agent N,N'-methylenebisacrylamide, heat to 50-60°C under inert gas protection, stir and react for 3-5 hours, pour into a mold, and UV-cure for 1-2 hours to obtain a mattress material based on natural mineral crystals.

8. A mattress material based on natural mineral crystals obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the mattress material based on natural mineral crystals as claimed in claim 8 in the preparation of a mattress.

Citation Information

Patent Citations

  • Negative ion far infrared nanometer multifunctional material

    CN106726628A

  • Porous magnetic adsorption material and preparation method thereof

    CN110252253A